Silene peloritana (Caryophyllaceae) a new species from Sicily - Brullo, Cristian; Brullo, Salvatore; Del Galdo, Gianpietro Giusso; Minissale, Pietro; Sciandrello, Saverio (Phytotaxa, 2014)
Silene peloritana is described and illustrated as a narrow endemic circumscribed to Mt. Scuderi, an isolated peak of the Peloritani range (NE Sicily). The new species, belonging to S. sect. Dipterosperma, is a small therophyte growing on cacuminal carbonatic stands. It is well differentiated from the other Sicilian species of this section for its small size, shorter lower internodes, bracts and calyx teeth, petal lobes obovate, coronal scales purplish, and anthers pinkish-violet. A key of the Sicilian taxa belonging to Silene sect. Dipterosperma is provided.